2019
DOI: 10.1017/jie.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

The importance of Aboriginal Education Workers for decolonising and promoting culture in primary schools: an analysis of the longitudinal study of Indigenous children (LSIC)

Abstract: Aboriginal Education Workers (AEWs) are utilised by primary and secondary schools to improve components of success for Aboriginal students, liaise with their families and the Aboriginal community and contribute to developing and promoting an Aboriginal pedagogy. Despite the challenging role of decolonising the school environment, the important work undertaken by AEWs can be misunderstood and underappreciated by the Western school system. This paper aims to measure the influence of AEWs on Aboriginal culture wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Importantly, the complex intersectionality between race/ethnicity, gender and poverty is rarely addressed [ 36 ], with Aboriginal and Torres Strait Islander students having the added overlay of colonisation impacts (including racism, segregation, dispossession, and forced disconnection from culture). Targeted school approaches to support Aboriginal and Torres Strait Islander students’ academic and social connections are gaining greater attention, with schools that recognise poverty as a contributing factor showing some gains [ 37 , 38 ]. No comparative Australian or international research examining child resilience by gender was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the complex intersectionality between race/ethnicity, gender and poverty is rarely addressed [ 36 ], with Aboriginal and Torres Strait Islander students having the added overlay of colonisation impacts (including racism, segregation, dispossession, and forced disconnection from culture). Targeted school approaches to support Aboriginal and Torres Strait Islander students’ academic and social connections are gaining greater attention, with schools that recognise poverty as a contributing factor showing some gains [ 37 , 38 ]. No comparative Australian or international research examining child resilience by gender was identified.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, over the last two decades, there has been an increasing effort to rectify the shortcomings of the primary, secondary, and tertiary education systems by decolonising and Indigenising curricula and education structures, and the training and employment of Indigenous professional and academic staff (Price, 2012;Trudgett, Page, & Coates, 2022;Universities Australia, 2017). To achieve this, measures have included greater recruitment and retention of Indigenous teachers (Andersen, O'Dowd, & Gower, 2015;Universities Australia, 2017), the employment of Aboriginal Education Workers (AEWs) (Peacock & Prehn, 2019;Price et al, 2017), decolonising and Indigenising the curriculum (Bodkin-Andrews et al, 2021;Hart et al, 2012;Nakata, 2010;Page et al, 2019;Prehn et al, 2020), and Indigenous cultural activities and pro-1 From this point on, Aboriginal and Torres Strait Islander and Indigenous international First Nations Peoples will be referred to as Indigenous peoples. With the Australian Anglo-colonised context Aboriginal is an aggregated descriptor for many unique Indigenous peoples with their own distinct identity, cultural practices, customs, lore, and histories (Dudgeon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies that have considered the experiences of Indigenous people's voices in education systems and the challenges and successes they experience when trying to meet the demands of policy, role statements and strategies in Western education systems (Shay & Wickes, 2017) and the initial experiences of AEOs in schools from their perspective. Evidence has shown that AEOs are key contributors to Indigenous educational outcomes (Andersen et al, 2015;Peacock & Prehn, 2019), however, at times some of this research has only included the voices of non-Indigenous teachers, policy makers and researchers (Armour, 2016) meaning that AEOs' voices have generally remained unheard, and this privileges insights into AEOs' roles from a non-Indigenous perspective. In particular, how AEOs understand their role, what they do in this role, the support they provide for schools, the experiences they have had in schools and how they switch between two knowledge systems (Indigenous and Western) when working in school contexts.…”
Section: Introductionmentioning
confidence: 99%